Elements of a Critical Theory of Justice - Pereira, Gustavo. author. aut Link
VIII, 246 p.
Keywords: The capacity to take part in dialogues and justify one's positions constitutes the normative core of critical social justice. Ensuring this capacity to every citizen is the main objective of justice, which requires transforming social structures and relations as well as counteracting the effects of capitalist dynamics. .